Improving Heart Failure Outcomes with Education - Sheppard, Tonya (My University, 2023)
Heart Failure is a global healthcare priority, with tens of millions diagnosed worldwide. The cost of caring for these chronically ill patients will rise exponentially over the next few years with expanding and aging populations and the latest medical treatments being made available in most corners of the world. Without adequate and extensive interventions, this will become a worldwide healthcare crisis by 2030. Treatments have become more complex and effective, but without patient adherence to their self-care regimen and participation in their care, any treatment plan is doomed to fail. This project explored the effect of robust patient education and continued close follow-up on patient adherence, treatment success, quality of life, and healthcare outcomes. By empowering the patient with resources, including their support system, and keeping them accountable for their participation, patient adherence to their self-care regimen improved, as did their symptom management and quality of life. This improvement has significant implications not only for the patients, but also for nursing practice and healthcare systems.
Keywords: heart failure, heart failure outcomes, heart failure education, heart failure self-care